Implementasi Kurikulum Muatan Lokal Bahasa Sunda Sebagai Upaya Pelestarian Budaya di Sekolah Dasar - Mafaz Al-Akmam; Dhea Adela (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2026)
The decadence in the existence of regional languages in the modern era requires educational institutions to take part in efforts to preserve local culture, one of which is by introducing regional languages from an elementary school age. This research aims to explore the implementation of the Sundanese language local content curriculum in elementary schools through learning activities and cultural preservation programs. Using a qualitative approach to case study design, data was collected through observation, interviews, and documentation, then analyzed using interactive analysis techniques and tested for data validity using the Triangulation Technique and Source. The results of the study show that SD Negeri 5 Caringin actively implements the local content curriculum through three stages, namely: learning planning through the preparation of learning administration, the implementation of learning with various methods, and presenting learning media and resources that stimulate student activity and learning evaluation that shows the level of student understanding. In addition to formal learning, cultural preservation is strengthened through Sundanese language habituation programs and the use of traditional clothes on every Thursday, talent development, which is implemented by participating in several competitions and activities that carry local cultural themes, as well as commemoration of national holidays that are complementary in the introduction of Saunda culture in the school environment. Through this curriculum, the school succeeds in instilling local cultural values and providing students with a deep understanding of cultural richness. It was concluded that the school has created an environment that supports efforts to preserve Sundanese culture effectively, both in the school environment and in the community.